8 - Demise or Resilience, Customary Law and the Changing Order in Africa: The Case of Chieftaincy in Botswana: DOI: 10.4314/ad.v30i4.22245 - Morapedi, Wazha G. (Africa Development, 2005)
This paper reviews customary law and how it relates to the institution of Chieftainship in Botswana from the pre-colonial to the post colonial period. It accedes to the widely held view that in Botswana, as in many other African countries where the institution of chieftainship was undermined by colonial rule, chiefs have survived and continues to play a pivotal role in evolving African societies. In Botswana, customary laws governing the institution of the chieftainship, particularly the succession rules, have enabled the chieftainship to surmount the hurdles placed against chiefs by the colonial government. The colonial government onslaught on chieftainship only weakened some chiefs, but not the institution. Since 1966 the post-colonial liberal democratic govern ment of Botswana has continued to enact laws which whittled down the powers of the chiefs considerably, but the institution has adapted and chiefs have also managed to manipulate the political situation to their advantage. Today, due to the dynamism of customary law, chiefs play a pivotal role in the socio-eco nomic, political and administrative systems of Botswana